2024
DOI: 10.2174/1574888x19666230905114246
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Central and Nasal Orbital Adipose Stem Cells and their Neural Differentiation Footprints

Fatemeh Sanie-Jahromi,
M. Hossein Nowroozzadeh,
Mina Shaabanian
et al.

Abstract: Background: The unique potential of stem cells to restore vision and regenerate damaged ocular cells has led to the increased attraction of researchers and ophthalmologists to ocular regenerative medicine in recent decades. In addition, advantages such as easy access to ocular tissues, non-invasive follow-up, and ocular immunologic privilege have enhanced the desire to develop ocular regenerative medicine. Objective: This study aimed to characterize central and nasal orbital adipose stem cells (OASCs) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The topography of the cellular microenvironment plays a vital role in Frontiers in Bioengineering and Biotechnology frontiersin.org cell activities, guiding cell attachment, morphology, proliferation, and differentiation. Furthermore, it influences cell signaling and morphology Cells can sense morphological changes in the extracellular matrix of cells and convert this information into morphological changes, thereby affecting cell differentiation (Sanie-Jahromi et al, 2023). In 2010, Yin Zi's team introduced bioengineered scaffolds into the TDSCs research field by planting human-derived TDSCs on electrospun nanofiber scaffolds (Yin et al, 2010).…”
Section: Scaffoldsmentioning
confidence: 99%
“…The topography of the cellular microenvironment plays a vital role in Frontiers in Bioengineering and Biotechnology frontiersin.org cell activities, guiding cell attachment, morphology, proliferation, and differentiation. Furthermore, it influences cell signaling and morphology Cells can sense morphological changes in the extracellular matrix of cells and convert this information into morphological changes, thereby affecting cell differentiation (Sanie-Jahromi et al, 2023). In 2010, Yin Zi's team introduced bioengineered scaffolds into the TDSCs research field by planting human-derived TDSCs on electrospun nanofiber scaffolds (Yin et al, 2010).…”
Section: Scaffoldsmentioning
confidence: 99%
“…[ 13 ] Therefore, we can boldly speculate that the medial fat pad originates from neural crest that are different from the central fat pad. However, in the experiment of differentiation of orbital fat-derived stem cells into neural cells in vitro, stem cells from central fat pad expressed more marker antigens of neuronal and glial cell [ 11 ] ; while Sanie-Jahromi et al [ 14 ] pointed out that compared with central fat pad, adipose stem cells from medial fat pad have stronger neural differentiation ability. Gola et al [ 15 ] reported that medial fat pad of orbital fat is rich in fiber and blood vessels and is lobulated, while the central fat pad has less blood vessels and is liquid, similar to subcutaneous fat; Kim et al [ 16 ] studied the development of upper eyelid of human embryo and found that the central fat pad of upper eyelid began to differentiate at 16 weeks, and the preseptal fat located between orbicularis oculi muscle and orbital septum began to differentiate at 18 weeks, which may indicate that the origin of the above fat is different, but failed to find the difference in differentiation time between medial and central fat pad.…”
Section: Embryological Study Of Orbital Fatmentioning
confidence: 99%